Effects of walking in water on gut hormone concentrations and appetite: comparison with walking on land. Issue 1 (January 2018) - Ueda, Shin-ya; Nakahara, Hidehiro; Kawai, Eriko; Usui, Tatsuya; Tsuji, Shintaro; Miyamoto, Tadayoshi
Abstract : The effects of water exercise on gut hormone concentrations and appetite currently remain unclear. The aim of the present study was to investigate the effects of treadmill walking in water on gut hormone concentrations and appetite. Thirteen men (mean ± s.d. age: 21.6 ± 2.2 years, body mass index: 22.7 ± 2.8 kg/m 2, peak oxygen uptake (VO2peak ): 49.8 ± 7.8 mL/kg per min) participated in the walking in water and on land challenge. During the study period, ratings of subjective feelings of hunger, fullness, satiety and motivation to eat were reported on a 100-mm visual analog scale. A test meal was presented after walking, and energy intake (EI) was calculated. Blood samples were obtained during both trials to measure glucagon-like peptide-1 (GLP-1), peptide YY (PYY) and acylated ghrelin (AG) concentrations. Hunger scores (How hungry do you feel?) were significantly lower during the water trial than during the land trial ( P  < 0.05). No significant differences were observed in EI between water and land trials. GLP-1 concentrations were significantly higher in the water trial than in the land trial ( P  < 0.05). No significant differences were observed in PYY concentrations between water and land trials. AG concentrations were significantly lower in the water trial than in the land trial ( P  < 0.01). In conclusion, changes in gut hormone concentrations during walking in water contribute to the exercise-induced suppression of appetite and provide novel information on the influence of walking in water on the acute regulation of appetite.